THE ROLE OF ERP IMPLEMENTATION AS A MODERATION VARIABLE, THE INFLUENCE OF AUDIT COMMITTEE EXPERTISE ON THE TIMELINESS OF FINANCIAL STATEMENT DURING THE COVID-19 PANDEMIC - Herry Laksito (Riset Akuntansi Keuangan, 2021)
The purpose of this study was to examine the effect of the expertise of the auditcommittee members on the timeliness of financial reporting by implementingERP as a moderating variable. The independent variable used in this study isthe expertise of the audit committee members. While the dependent variableused in this study is the timeliness of financial reporting and the moderatingvariable in this study is the implementation of ERP. The population in thisstudy are companies listed on the IDX and included in the LQ45 stock index.The population used in this study were 44 companies. The results of this studyindicate that the expertise of the audit committee members has a positive andsignificant effect on the accuracy of the company's financial reporting. Theresearch result showed that the implementation of ERP weakened therelationship between the expertise of the audit committee members and thetimeliness of the company’s financial reporting.